Sacred text, sacred space: architectural, spiritual and literary convergences in England and Wales - Sterrett, Joseph; Thomas, Peter Wynn (Studies in religion and the arts 1877-3192, 2011)
Acknowledgements; List of Illustrations; Foreword; Introduction; Part One The Medieval Sacred; Images of Words: Iconographies of Text and the Construction of Sacred Space in Medieval Church Wall Painting; Anglo-Saxon Monasteries as Sacred Places: Topography, Exegesis and Vocation; The Book of the Foundation of St Bartholomew's Church: Consecration, Restoration, and Translation; An Arena for the Holy: The Imitatio Francisci of Margery Kempe; Part Two Re-Writing Sacred Space in the Early Modern Period; To Great Saint Jacques Bound: All's Well That Ends Well in Shakespeare's Spain